Long non-coding RNA stabilizes the Y-box-binding protein 1 and regulates the epidermal growth factor receptor to promote lung carcinogenesis - Wei, Ming-Ming; Zhou, Yong-Chun; Wen, Zhe-Sheng; Zhou, Bo; Huang, Yun-Chao; Wang, Gui-Zhen; Zhao, Xin-Chun; Pan, Hong-Li; Qu, Li-Wei; Zhang, Jian; Zhang, Chen; Cheng, Xin; et al. (Oncotarget, 2016)
Indoor and outdoor air pollution has been classified as group I carcinogen in humans, but the underlying tumorigenesis remains unclear. Here, we screened for abnormal long noncoding RNAs (lncRNAs) in lung cancers from patients living in Xuanwei city which has the highest lung cancer incidence in China due to smoky coal combustion-generated air pollution. We reported that Xuanwei patients had much more dysregulated lncRNAs than patients from control regions where smoky coal was not used. The lncRNA CAR intergenic 10 (CAR10) was up-regulated in 39/62 (62.9%) of the Xuanwei patients, which was much higher than in patients from control regions (32/86, 37.2%; p=0.002). A multivariate regression analysis showed an association between CAR10 overexpression and air pollution, and a smoky coal combustion-generated carcinogen dibenz[a,h]anthracene up-regulated CAR10 by increasing transcription factor FoxF2 expression. CAR10 bound and stabilized transcription factor Y-box-binding protein 1 (YB-1), leading to up-regulation of the epidermal growth factor receptor (EGFR) and proliferation of lung cancer cells. Knockdown of CAR10 inhibited cell growth in vitro and tumor growth in vivo. These results demonstrate the role of lncRNAs in environmental lung carcinogenesis, and CAR10-YB-1 represents a potential therapeutic target.